Comprehensive model for predicting the fuel consumption in various harvesting methods of grass silage - Jokiniemi, Tapani; Mikkola, Hannu; Hakojärvi, Mikko; Alakukku, Laura (Agricultural and Food Science, 2021)
Fuel consumption of various forage harvesting methods was assessed with a theoretical calculation model, which was validated with field measurements. The examined harvesting methods were tractor-powered forage harvester (TPFH), self-propelled forage harvester (SPFH), self-loading forage wagon (SLFW), and combined baling and wrapping (CBW). The results from the field measurements indicated that the model was working either well or satisfactorily with the examined methods, apart from the CBW method, which would require redefining the model coefficients. Model sensitivity analysis indicated that variables such as yield level, working width, and transportation distance have a significant effect on fuel consumption. When the working width was increased from 3 m to 9 m, the fuel consumption of the examined methods decreased ca. 54–61%. Increasing the working width by windrowing was found recommended for all examined methods. In all, the most energy-efficient method was SLFW, but it was also most sensitive to transportation distance. With a transportation distance of 10 km, the fuel consumption of the SLFW method was already 9–11 % higher compared to that of TPFH and SPFH methods. The strong effect of these variables may cause a wide variation in the fuel consumption of the examined methods, but the model can be used to standardize this effect. The results from this study can thus be used for approximate estimations of average fuel consumption of the examined forage harvesting methods.